2018
DOI: 10.1371/journal.ppat.1006871
|View full text |Cite
|
Sign up to set email alerts
|

Liver macrophage-associated inflammation correlates with SIV burden and is substantially reduced following cART

Abstract: Liver disease is a leading contributor to morbidity and mortality during HIV infection, despite the use of combination antiretroviral therapy (cART). The precise mechanisms of liver disease during HIV infection are poorly understood partially due to the difficulty in obtaining human liver samples as well as the presence of confounding factors (e.g. hepatitis co-infection, alcohol use). Utilizing the simian immunodeficiency virus (SIV) macaque model, a controlled study was conducted to evaluate the factors asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(46 citation statements)
references
References 104 publications
(106 reference statements)
2
44
0
Order By: Relevance
“…A recent study looking at myeloid-derived suppressor cells (MDSC) revealed that depletion of these cells in BM could contribute to systemic immune activation and exacerbate SIV pathogenesis (22). In our paper, we focus on the CD4 ϩ T cell contribution to viral persistence; however, others have shown that other cellular subsets in the bone marrow may harbor virus as well (23).…”
mentioning
confidence: 98%
“…A recent study looking at myeloid-derived suppressor cells (MDSC) revealed that depletion of these cells in BM could contribute to systemic immune activation and exacerbate SIV pathogenesis (22). In our paper, we focus on the CD4 ϩ T cell contribution to viral persistence; however, others have shown that other cellular subsets in the bone marrow may harbor virus as well (23).…”
mentioning
confidence: 98%
“…Other studies have hypothesized that HIV results in hepatocellular damage through cellular activation, although data on its potential to infect hepatocytes and Kuppfer cells are limited . Recent work using a simian immunodeficiency virus model in macaques suggested that macrophage and T cell activation were primary drivers of hepatic inflammation . In our analysis, ALT levels correlated with soluble CD163, a marker specific to activated macrophages that has been associated with Kupffer cell activation .…”
Section: Discussionmentioning
confidence: 50%
“…The microbiome is in uenced by numerous factors such as age, environment, food and antibiotics [25][26][27][28][29]. With regard to the liver during SIV infection, prior studies have identi ed elevated bacterial loads during SIV infection [30,31], as well as in the context of cART [32], and have shown that bacteria may increase immune cell in ltration [30]. During cART-treated SIV infection, the liver microbiome has been shown to be enriched for in ammatory Proteobacteria that preferentially translocate out of the gut and into the colonic lamina propria [24].…”
Section: Understanding Of the Gut Microbiome And Immune Changes Durinmentioning
confidence: 99%